Effects of Orem’s Self-Care Model on the Life Quality of Elderly Patients with Hip Fractures - Xiaodong Xu; Jun Han; Yajia Li; Xichun Sun; Peng Lin; Ying Chen; Fuqiang Gao; Zirong Li; Shuai Zhang; Wei Sun (Pain Research and Management)
Background. Hip fractures of elderly patients are a public health problem worldwide, mostly lying in bed for a long time; therefore, the importance of life quality in such patients is an issue beyond question. Orem’s self-care model is a nursing pattern which is introduced with the purpose of improving the self-care ability of individuals, especially the patients suffering from diseases with limits on activity. Objective. The aim of this study was to determine the effects of Orem’s self-care program on life quality of senile patients with hip fractures. Methods. A randomized clinical trial study was conducted on 130 eligible old patients suffering from hip fractures who were selected using easy sampling methods and allocated randomly into two groups of experiment and control. The data were collected through validated questionnaires including visual analogue scale (VAS) and Barthel index for them. The experiment group was treated according to Orem’s self-care model, and the control group was treated on the basis of the traditional care model. The data of complications including pneumonia, deep venous thrombosis, urinary infection, wound problem, and bedsore were also gathered. Results. As revealed, mean scores of VAS and Barthel index one week after operation in the experiment group were significantly different from the control one (P<0.05, P≤0.001). The changes of VAS and Barthel index six weeks postoperatively of the two groups were also statistically significant (P<0.05, P≤0.001). Compared with the control group, the difference of complications reduced significantly in the experiment group (P<0.05). Accordingly, educational intervention according to Orem’s self-care model seemed to be effective in promoting self-care ability for these senile patients. Conclusions. According to the obtained results, a self-care program based on Orem’s model for elderly patients with hip fractures can improve life quality and reduce perioperative complications significantly. Therefore, it is recommended that this nursing program should be taken into account as a part of treatment measures for these patients.